2009
DOI: 10.1111/j.1528-1167.2008.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

A substantial number of Rasmussen syndrome patients have increased IgG, CD4+ T cells, TNFα, and Granzyme B in CSF

Abstract: Summary Purpose:  We studied the immunologic molecules in cerebrospinal fluid (CSF) and discussed their evolutional changes in pediatric patients with Rasmussen syndrome (RS). Methods:  CSF samples collected from 27 patients with RS (average onset age, 7.5 ± 5.6 years) were studied. Cell count, protein, glucose, albumin, chloride, and immunoglobulin G (IgG) levels were measured by conventional methods. Surface markers of lymphocytes in CSF were examined by a cell sorter. Granzyme B, interferon γ (IFNγ), interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 41 publications
3
51
1
2
Order By: Relevance
“…Granzyme A produced by CD8 + and NK cells could be involved in cytokine production and apoptotic response in epilepsy. Interestingly, in Rasmussen encephalitis, granzyme B and TNF were increased in the CSF [19].…”
Section: Inflammatory Association With Clinical Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Granzyme A produced by CD8 + and NK cells could be involved in cytokine production and apoptotic response in epilepsy. Interestingly, in Rasmussen encephalitis, granzyme B and TNF were increased in the CSF [19].…”
Section: Inflammatory Association With Clinical Findingsmentioning
confidence: 96%
“…DAMPs generated in the brain after seizures would induce a cascade of events leading to local and systemic inflammation ( Figure 9). Indeed experimental studies have demonstrated that there is continuous recruitment of peripheral cells into the brain following seizures, with a parallel between the activation of immune cells in the CNS and in the periphery [3,[19][20][21][22].…”
Section: Inflammatory Association With Clinical Findingsmentioning
confidence: 99%
“…In addition to plasma, GrB is also present in the synovial fluid (SF) of rheumatoid arthritis (RA) patients, the cerebrospinal fluid (CSF) of multiple sclerosis (MS) and Rasmussen encephalitis patients, as well as the bronchoalveolar lavage (BAL) in chronic obstructive pulmonary disease (COPD) and lung inflammation. [122][123][124][125] Although the GrB inhibitor PI-9 is present in normal human plasma, GrB retains 70% of its activity in the plasma, suggesting that PI-9 does not efficiently inhibit GrB activity in the blood. 126,127 There is a lack of evidence for an endogenous extracellular GrB inhibitor that is physiologically effective, thus its extracellular activity may be largely unregulated in contrast to other ECM proteases such as MMPs, which are tightly regulated by the tissue inhibitors of metalloproteases.…”
Section: Extracellular Grb Activitymentioning
confidence: 99%
“…This study advanced the authors to the idea of having pronounced Th1 immune response in the early phase of the disease that declines 1 to 2 years in the disease course. Since the higher levels of IFN-γ in cerebrospinal fluid in the earlier stages of RE was reported by Takahashi et al [14], detection of large numbers of CD4+ and CD8+ lymphocytes from the same specimen from which the high levels of IFN-γ were detected, are consistent with an initial Th1 response.…”
Section: Rasmussen's Encephalitismentioning
confidence: 54%